Wie ist die Welt zu erklären, wenn sie einer Erklärung bedarf? - Hermanni, Friedrich (Neue Zeitschrift für systematische Theologie und Religionsphilosophie, 2022)
The essay explores in four steps the question of whether the world needs an explanation and how it is to be explained in the case of its need for explanation. The first step argues that the principle of sufficient reason is valid and may be applied to the world as a whole. The three following steps examine different possibilities of explaining the world. It is shown that neither an immanent nor an axiogenetic explanation is possible, but that only an ontotheological explanation has a chance of success.